Economists, parsifal and the search of holy grail (1997)
The economics profession finds itself unsatisfied with the state of economic theory. The most prestigious economists are the main critics of formalism and the abuse of mathematics, despite the success they have had doing what they now criticize in their Nobel speeches. This article analyzes why economists do not ask the pertinent questions from the outset of their careers, using an interpretation of the myth of the Holy Grail based on the psychology of Carl Jung. It compares the formation of economists with the formation of the knights of the middle ages and shows that one of the socioloqical reasons for excessiveformalism is that scientists seek not only the truth, but also theapproval of other scientists.